Adipose-Derived Stem Cells Promote Bone Coupling in Bisphosphonate-Related Osteonecrosis of the Jaw by TGF-β1 - Dong, Xian; He, Linhai; Zang, Xiaolong; He, Yang; An, Jingang; Wu, Baoping; Liu, Xinhua; Bi, Hongsen; Zhang, Yi; Xiao, E. (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to investigate molecularly targeted therapy to revive bone remodeling and prevent BRONJ by local adipose-derived stem cells (ADSCs) transplantation. Clinical samples of BRONJ and healthy jawbones were used to examine the bone coupling-related cells and TGF-β1 expression. Bone coupling-related cells and TGF-β1 expression were also assessed in BRONJ-like animal model to confirm the results in clinical samples. ADSCs were locally administered in vivo and the therapeutic effects were evaluated by gross observation, radiological imaging, and histological examination. Furthermore, ADSCs-conditioned medium (ADSCs-CM) and neutralizing antibody were applied to assess the effects of ADSCs-derived TGF-β1 on restoring bone coupling in vivo. Osteoclast formation and resorption assays were performed to evaluate the effects of ADSCs-derived TGF-β1 on ZA-treated pre-osteoclasts. Cell migration was performed to assess the effects of ADSCs-derived TGF-β1 on patients’ bone marrow stem cells (BMSCs). The number of osteoclasts, Runx2-positive bone-lining cells (BLCs) and TGF-β1 expression were decreased in BRONJ and animal model jaw bone samples. These reductions were significantly rescued and necrotic jawbone healing was effectively promoted by local ADSCs administration in BRONJ-like animal models. Mechanistically, ADSCs-CM mainly contributed to promoting bone coupling, while TGF-β1 neutralizing antibody in the conditioned medium inhibited these effects. Besides, osteoclastogenesis and patients’ BMSCs migration were also rescued by ADSCs-derived TGF-β1. Furthermore, bone resorption-released bone matrix TGF-β1, together with ADSCs-derived TGF-β1, synergistically contributed to rescuing BMSCs migration. Collectively, ADSCs promoted bone healing of BRONJ by TGF-β1-activated osteoclastogenesis and BMSCs migration capacities.